2019
DOI: 10.1101/631135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced biodegradation of naphthalene byPseudomonassp. consortium immobilized in calcium alginate beads

Abstract: Polycyclic aromatic hydrocarbons (PAHs) belong to a large group of organic pollutant which considers as a potential health hazard to living beings. Herein, naphthalene biodegradation potential by free and immobilized Pseudomonas putida strain KD10 and Pseudomonas sp. consortium were studied. Additionally, naphthalene 1, 2-dioxygenase (nahAc) was sequenced and analyzed, which reveals two altered amino acid residues. However, the altered amino acid residues are not present in the vicinity of the active site. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Commonly PAHs degradation is initiated by ring hydroxylating dioxygenase [136]. Naphthalene degradation in Pseudomonas putida KD10 follows the metacleavage pathway of catechol [137]. Stenotrophomonas maltophilia C6 possesses multiple degradation pathways for phenanthrene [138].…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Commonly PAHs degradation is initiated by ring hydroxylating dioxygenase [136]. Naphthalene degradation in Pseudomonas putida KD10 follows the metacleavage pathway of catechol [137]. Stenotrophomonas maltophilia C6 possesses multiple degradation pathways for phenanthrene [138].…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…This enhancement could be achieved by several ways such as, different biodegradation pathways of each individual bacterium, metabolic intermediates of one bacterium that may act as the starting material of another, different genetic makeup, or by synthesising different variants of the same catalytic enzymes (Obayori et al, 2009;Kumari et al, 2018). Re cently, Dutta et al (2019) have reported that a microbial consortium of Pseudomonas sp. may be superior to the free Pseudomonas strains in polycyclic aromatic hydrocarbon biodegradation since the epigenetic impacts on the metabolic enzymes.…”
Section: Biodegradation Experimentsmentioning
confidence: 99%